ANALYSIS OF THE INFLUENCE OF SAFETY LEADERSHIP ON SAFETY BEHAVIOR THROUGH SAFETY AWWERNES, SAFETY CLIMATE, SAFETY CITIZEN BEHAVIOR AT BOEKIT TAWAP SARONGGI TOURISM OBJECTS - Sadili, Fery; Faidal, Faidal (Dynamic Management Journal, 2024)
The aim of conducting research at the Boekit Tawap Saronggi tourist attraction is to find out the impact of Safety Leadership on Safety Behavior through Safety Awwerness, Safety Climate, SCB. This research uses quantitative methods through questionnaires. (1) Safety Leadership has a direct and significant effect on Safety Behavior, as evidenced by the results of the t test of Equation II with a calculated t result of 6.083 and a significance result of 0.000 <0.05 and a regression coefficient of 0.585; (2) Safety Leadership has a direct effect on safety awareness, safety climate, SCB as shown by the results of the t test of Equation I with a t count of 11.829 and a significance of 0.000 < 0.05 and a regression coefficient of 0.457; (3) Safety Awwernes, Safety Climate, SCB have a significant effect on Safety Behavior as indicated by the results of the t test of Equation II with a t count of 1.473 and a significance result of 0.145 > 0.05 and a regression coefficient result of 0.142; (4) Safety Leadership has an indirect influence on Safety Behavior through Safety Awwerness, Safety Climate, SCB which is indicated by an indirect influence coefficient of 0.064; Safety Aweness, Safety Climate, SCB are able to mediate the influence of Safety Leadership on Safety Behavior, as evidenced by the results of the Sobel test which has a result of 0.439 > 0.010.